DEVELOPMENT OF PISA TYPES OF QUESTIONS AND ACTIVITIES CONTENT SHAPE AND SPACE CONTEXT PANDEMIC PERIOD - Risda Intan Sistyawati; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Samsuriyadi Samsuriyadi; Zahra Alwi; Sisca Puspita Sepriliani; Ayu Luviyanti Tanjung; Riszky Pabela Pratiwi; Shinta Aprilisa; Duano Sapta Nusantara; Meryansumayeka Meryansumayeka; Jayanti Jayanti (IKIP Siliwangi and I-MES, 2023)
This research belongs to the type of development research, which consists of the main stages, including preliminary design and formative evaluation. This study aims to obtain valid and practical PISA-type development questions consisting of initial design, self-evaluation, expert review, one-to-one, and small group. The emergence of this research is due to the low mathematical literacy of students in Indonesia. This study took a particular research subject for grade IX junior high school students in Palembang City. From this study, the results obtained include the development of PISA-type questions and activities using the context of social distancing during the pandemic.